Cellulitis in children: a retrospective single centre study from Australia - Barbara King; Asha C Bowen; Elise Salleo; Conor I MacKay; Jeffrey Cannon (BMJ Publishing Group, 2021)
Aim To characterise the epidemiology, clinical features and treatment of paediatric cellulitis.Methods A retrospective study of children presenting to a paediatric tertiary hospital in Western Australia, Australia in 2018. All inpatient records from 1 January to 31 December 2018 and emergency department presentations from 1 July to 31 December 2018 were screened for inclusion.Results 302 episodes of cellulitis were included comprising 206 (68.2%) admitted children and 96 (31.8%) non-admitted children. The median age was 5 years (IQR 2-9), 40 (13.2%) were Aboriginal and 180 (59.6%) boys. The extremities were the most commonly affected body site among admitted and non-admitted patients. There was a greater proportion of facial cellulitis in admitted patients (27.2%) compared with non-admitted patients (5.2%, p<0.01). Wound swab was the most frequent microbiological investigation (133/302, 44.0%), yielding positive cultures in the majority of those tested (109/133, 82.0%). The most frequent organisms identified were Staphylococcus aureus (94/109, 86.2%) (methicillin-susceptible S. aureus (60/94, 63.8%), methicillin-resistant S. aureus) and Streptococcus pyogenes (22/109, 20.2%) with 14 identifying both S. aureus and S. pyogenes. Intravenous flucloxacillin was the preferred antibiotic (154/199, 77.4%), with median intravenous duration 2 days (IQR 2-3), oral 6 days (IQR 5-7) and total 8 days (IQR 7-10).Conclusions Cellulitis is a common reason for presentation to a tertiary paediatric hospital. We confirm a high prevalence of extremity cellulitis and demonstrate that children with facial cellulitis often require admission. Cellulitis disproportionately affected Aboriginal children and children below 5 years. Prevention of cellulitis involves early recognition and treatment of skin infections such as impetigo and scabies.